Residential proximity to industrial zones and self-reported respiratory morbidity: a community-based cross-sectional survey of three Karachi industrial areas - Shahbaz, Kiran; Shaikh, Shiraz; Nighat, Aroosa; Khan, Irfanullah; Ullah, Mehran; Shaheen, Farkhanda (Frontiers in Public Health, 2025)
BackgroundIndustrial emissions in Karachi contribute to poor ambient air quality and may adversely affect nearby residents’ respiratory health. This study assessed whether residential distance from industrial zones is associated with respiratory symptoms and chronic respiratory disease.MethodsWe conducted a comparative, community-based cross-sectional survey (March–August 2024) of 462 adults sampled equally around three industrial zones S. I. T. E., Korangi, and Landhi (n = 154 each). Residential distance to the nearest industrial zone was classified as within 5 km vs. more than 5 km (distance estimated from mapped home addresses). Respiratory outcomes (symptoms; chronic bronchitis; asthma) were obtained via a validated questionnaire, and multivariable logistic regression estimated adjusted associations. This was a cross-sectional, community-based study using self-reported data without clinical assessments.ResultsCompared with residents living more than 5 km away, those living within 5 km reported substantially higher prevalences of cough, phlegm, wheeze, and dyspnea. Living more than 5 km from an industrial zone was independently associated with markedly lower odds of chronic bronchitis (adjusted OR 0.09, 95% CI 0.02–0.72) and asthma (adjusted OR 0.14, 95% CI 0.03–0.67). Higher education was protective for both outcomes, and regular mask use was protective for chronic bronchitis; smoking and industrial employment were associated with greater respiratory morbidity.ConclusionIn Karachi, residing within 5 km of major industrial zones is linked to a higher burden of self-reported respiratory symptoms and chronic respiratory disease. These findings underscore the importance of early screening and preventive strategies for nearby communities and support zoning and urban-planning measures that increase residential buffers from industrial facilities.